2012
DOI: 10.1016/j.neuroscience.2012.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to defeat ketamine-induced neonatal brain injury

Abstract: Studies using animal models have shown that general anesthetics such as ketamine trigger widespread and robust apoptosis in the infant rodent brain. Recent clinical evidence suggests that the use of general anesthetics on young children (at ages equivalent to those used in rodent studies) can promote learning deficits as they mature. Thus, there is a growing need to develop strategies to prevent this injury. In this study, we describe a number of independent approaches to address therapeutic intervention. Post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 60 publications
2
41
0
Order By: Relevance
“…Thus, the search for adjunctive neuroprotective measures that will prevent or ameliorate the toxicity of ketamine in the developing human brain is highly warranted. Although many strategies, including the use of the activity-dependent neuroprotective protein peptide fragment NAPVSIPQ (NAP) (Turner et al, 2012), vitamin D (Turner et al, 2012), lithium (Straiko et al, 2009), erythropoietin (Shang et al, 2007), L-carnitine (Liu et al, 2013), nicotinamide (Ullah et al, 2012), and clonidine (Ponten et al, 2012), are known to have neuroprotective effects against ketamine-induced apoptosis both in vivo and in vitro, their efficacy and safety need to be further verified for uses targeting the developing brain.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the search for adjunctive neuroprotective measures that will prevent or ameliorate the toxicity of ketamine in the developing human brain is highly warranted. Although many strategies, including the use of the activity-dependent neuroprotective protein peptide fragment NAPVSIPQ (NAP) (Turner et al, 2012), vitamin D (Turner et al, 2012), lithium (Straiko et al, 2009), erythropoietin (Shang et al, 2007), L-carnitine (Liu et al, 2013), nicotinamide (Ullah et al, 2012), and clonidine (Ponten et al, 2012), are known to have neuroprotective effects against ketamine-induced apoptosis both in vivo and in vitro, their efficacy and safety need to be further verified for uses targeting the developing brain.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous animal studies in rodents indicate that ketamine induces neurodegeneration in the developing brain in a dose-depended manner, and the data also suggest that limiting exposure limits the potential for neurodegeneration. Some postnatal preclinical studies suggested that ketamine-induced injury in the infant rodent brain was a centrally driven event [24,25] . There are very few studies that have examined the potential functional consequences of the neurodegeneration noted in the animal models, except recent evidence suggests that multiple exposures to anesthetics (including ketamine) and surgery before the age of 2 was a significant independent risk factor for the later development of learning disabilities [26] .…”
Section: Side Effectsmentioning
confidence: 99%
“…Ketamine is a non-competitive N-methyl-D-aspartate (NMDA) antagonist that disrupts calcium homeostasis in neurons (Sinner et al, 2005;Slikker et al, 2007). Since calcium signaling has an important role in cytoskeleton stability (Lankford and Letourneau, 1989) as well as neuronal viability (Turner et al, 2007;Ringler et al, 2008), ketamineinduced calcium deregulation may lead to alterations in axonal outgrowth and induction of apoptotic cell death (Wang et al, 2005;Turner et al, 2012;Bai et al, 2013;Dong and Anand, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This study investigated the dual role of ketamine, as both a neurotoxin in some animal models (Wang et al, 2005;Slikker et al, 2007;Turner et al, 2012;Bai et al, 2013), and as a neuroprotectant in other animal models Rovnaghi et al, 2008;Turner et al, 2012). Depending on the dosage, ketamine has been demonstrated to be protective as well as destructive to certain brain regions.…”
Section: Introductionmentioning
confidence: 99%